الهندسة الاجتماعیة وشبکات التواصل الاجتماعى وتاثیرها على المجتمع العربى - د. مها أحمد ابراهیم (المجلة الدولية لعلوم المكتبات والمعلومات)
The present study aims at recognizing to an extreme the Arab communityis aware of how to protect their accounts and ways of penetration (hacking) ofprivacy on a general level and focusing on social engineering on particular. Inaddition to other available ways of training the digital citizen. The concept ofsocial engineering (the art of penetrating minds), the significance of socialnetworks in the Arab world, and the importance of privacy from social networks'users in the Arab world, as well as recognizing ways of social networkspenetration and ways of social engineering protection. So we can point out thatthe Arab community awareness of social engineering is one of its priorities forprotecting their accounts in all social networks and the required skills to preventattacks of this social engineering in all social networks. A sample of 336individuals was applied to the current study. The study also comes up with thefollowing results: positively, individuals of the academic community succeeded atprotecting their data automatically and at a high rate. Selection of fake namesconstitutes half of the academic community ( 53.2%), who use social networksand this is explored by their deny of personal data or by writing fake personaldata. In addition to hacking their banking accounts since 6.8% of the individualswere slightly hacked. One of the most common methods of social engineeringattacks are spam messages sent by a friend as congratulations (77.1%), followedby 53.2% who are convinced by the significance of programs to be downloaded,the importance of social networks in the Arab world, the importance of privacyfrom users' point of view of social networks in the Arab world, as well as theidentification of penetrate ways of the social networks and how to be protectedfrom social engineering.